Cardiac Air Embolism in Neonates: A Hemodynamic Perspective - Louis, Deepak; Amer, Reem; Elsayed, Yasser N. (American Journal of Perinatology, 2018)
Cardiac air embolism should be suspected in any neonate with acute unexplained cardiovascular collapse or worsening oxygenation. We present here five cases that presented with the above symptoms. A comprehensive evaluation including targeted neonatal echocardiography and near-infrared spectroscopy helped confirm the diagnosis and assess the hemodynamic state. Management was supportive including left lateral positioning, chest compressions, and cardiovascular medications to treat pulmonary hypertension and systemic hypotension.
Keywords: air embolism; neonate; targeted neonatal echocardiography; cardiovascular collapse; pulmonary hypertension